Digital Governance Technologies for Fiscal Transfer Accountability: A Systematic Review - Fitriany Farhas; Widya Setiabudi Sumadinata; Febriyanto Febriyanto (Universitas Pendidikan Ganesha, 2026)
Fiscal decentralization confronts persistent challenges of corruption, fund misallocation, and accountability gaps in intergovernmental transfers. Digital governance technologies offer transformative potential; however, evidence regarding their effectiveness remains fragmented and has yet to be systematically synthesized. This study conducts a systematic literature review following the PRISMA 2020 guidelines with a TCCM (Theory–Context–Characteristics–Methodology) analytical framework to address how digital governance technologies enhance transparency and accountability in intergovernmental fiscal transfer systems. The review covers studies published between 2014 and 2025, retrieved from Scopus and Web of Science (WoS). Searches across these databases yielded 22 final articles from an initial pool of 182 records. All included studies reported positive impacts on fiscal transparency; however, this pattern may reflect potential publication bias. While e‑governance platforms, FMIS, and digital audit systems emerged as the dominant instruments, their effectiveness remains contingent upon institutional ecosystem factors such as human resource capacity, regulatory frameworks, political commitment, and organizational culture affirming that digital technologies represent a necessary but not sufficient condition. This study identifies significant theoretical gaps in Principal–Agent Theory and Technology Adoption Theories, a paradigmatic shift from reactive to preventive control, conflict settings as a new frontier, and the risk of the digital divide as a reproduction of inequality. Importantly, this study is the first to systematically map digital governance technologies specifically within intergovernmental fiscal transfer accountability using the TCCM (Theory–Context–Characteristics–Methodology) framework. These findings provide an evidence‑based foundation for policy development and future research agendas.